The growth impact of disasters in developing Asia - Suzette Dagli; Benno Ferrarini (Asian Development Bank (ADB), 2019)
This paper estimates the growth impact of disasters, with a focus on developing Asia and its subregions. It finds that severe disasters slow down annual growth in the Pacific island countries by between 1 and 2 percentage points on average. This should come as no surprise, given these economies' extreme exposure, structural vulnerability, and small size relative to the footprint of major natural hazards. The growth impact is less clear for other regions and worldwide, mainly because disaster effects tend to be highly localized and get diluted in the context of cross-country regressions with nationwide growth as the unit of analysis.
Keywords: O47; Q51; Q54; 330; developing Asia; disasters; economic growth; natural hazards